Engineering tendon and ligament tissues : present developments towards successful clinical products - Rodrigues, Márcia T. (2013)
Musculoskeletal diseases are one of the leading causes of disability worldwide. Among them, tendon and ligament injuries represent an important aspect to consider in both athletes and active working people. Tendon and ligament damage is an important cause of joint instability, and progresses into early onset of osteoarthritis, pain, disability and eventually the need for joint replacement surgery. The social and economical burden associated with these medical conditions presents a compelling argument for greater understanding and expanding research on this issue. The particular physiology of tendons and ligaments (avascular, hypocellular and overall structural mechanical features) makes it difficult for currently available treatments to reach a complete and long-term functional repair of the damaged tissue, especially when complete tear occurs. Despite the effort, the treatmentmodalities for tendon and ligament are suboptimal, which have led to the development of alternative therapies, such as the delivery of growth factors, development of engineered scaffolds or the application of stem cells, which have been approached in this review.